Pengaruh Sektor Ekonomi Perbankan Terhadap Pembentukan Modal di Indonesia - Aini, Huril; Tohirin, Ahmad (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2022)
This research aimed to know the credit and economic sector financing of banking economy effect on capital formation in Indonesia. The more investments that banks receive from investors, the more profits they will get in the future. In this case capital formation can develop. The research type is descriptive quantitative research. This research involved Islamic Commercial Bank, Islamic Business Unit, Conventional Banking and used monthly data in 2015-2020. This research used Autoregressive Distributed Lag (ARDL) to verify short term or long term correlation of independent variables on capital formation in Indonesia. The results of this research show that the short term variables of the agricultural sector and the manufacturing sector have no effect on capital formation. While, foreign direct investment has an effect on capital formation in Indonesia. Then in the long term, the agricultural sector has not effect on capital formation. While, the manufacturing sector and foreign direct investment have a direct effect on capital formation in Indonesia. Therefore recommended that the monetary authority make efforts effectively manage bank maximal loans.